Effect of blended learning on students' achievement in senior secondary geography in Niger state, Nigeria / Abubakar Yahaya Ibrahim - Ibrahim, Abubakar Yahaya (2019)
This study examined the effect of blended learning (BL) on students' achievement in Senior Secondary Geography. Three research questions and three hypotheses guided the study. Quasi - experimental was used for the study carried out in Minna, Bida and Suleja Education Zones in Niger State. The population of the study was 3.600 SS2 - Geography students. Six schools purposively selected from the three zones. The sample for the study was 390 SS2 Geography students consisting of 300 male and 90 females. The instrument for data collection was Geography Achievement Test (GAT). The GAT was used for the pre-test, post-test achievement test in geography using BLM. Digital Video Disk Instruction (DVDI), over head projector instruction (OHPI), face-to-face lecture method (blended together). The test items were validated. The coefficient of 0.81 was obtained for GAT using Kuder - Richardson (K - 21). The research questions were answered using mean (x) and standard deviation (SD) while analysis of covariance (ANCOVA) was used to test the hypotheses at 0.05 significant level. The result reveled that students exposed to BLM achieved higher post-test mean score than those exposed to lecture method. However, there is significant difference between the mean achievement scores of students taught geography with BLM and those taught with lecture method. BLM also enhanced higher level ability (HLA) and low level ability (LLA) students' achievement. The study revealed a significant difference in the mean (x) achievement score of male and female students subjected to BLM. Thus, this study recommended that teachers should adopt the use of blended learning method in teaching since its use in geography was found to be more effective than the lecture method and that the method be applied to other subjects in Secondary Schools.